Compatibility of Bangladesh railway's locomotives spare parts current recoupment policy in present situation and assess efficiency and effectiveness of procurement function. - Akbar, S.M. Rashed Ibney (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.